The Chinchilla Rabbits (Egypt) - El Raffa A.M.; Kosba M.A. (Rabbit genetic resources in Mediterranean countries, 2002)
A description of the Egyptian adapted breed of rabbit, Chinchilla, is carried out. Items that have been dealt with are: (i) a general description; (ii) climate and main features of its farming; (iii) performance; and (iv) stress resistance.